More Pronounced Hypercoagulable State and Hypofibrinolysis in Patients With Cirrhosis With Versus Without HCC. Issue 12 (16th August 2021) - Zanetto, Alberto; Campello, Elena; Bulato, Cristiana; Gavasso, Sabrina; Saggiorato, Graziella; Shalaby, Sarah; Spiezia, Luca; Cillo, Umberto; Farinati, Fabio; Russo, Francesco Paolo; Burra, Patrizia; Senzolo, Marco; et al.
Abstract : In patients with cirrhosis, particularly those with hepatocellular carcinoma (HCC), hypercoagulability may be associated with purported increased risks of portal vein thrombosis and cirrhosis progression. In this study, we extensively investigated hemostatic alterations potentially responsible for the thrombotic tendency in HCC, and evaluated whether such alterations were predictive of hepatic decompensation. Patients with cirrhosis at all stages were prospectively recruited and underwent an extensive hemostatic assessment, including all procoagulant factors and inhibitors, thrombin generation with and without thrombomodulin (TG), profibrinolytic and antifibrinolytic factors, and plasmin‐antiplasmin complex. In study part 1 (case control), we compared alterations of coagulation and fibrinolysis in patients with cirrhosis with versus without HCC. In study part 2 (prospective), the subgroup of patients with decompensated cirrhosis was followed for development of further decompensation, and predictors of outcome were assessed by multivariate analysis. One‐hundred patients were recruited (50 each with and without HCC). Severity of cirrhosis was comparable between groups. Median HCC volume was 9 cm 3 (range: 5‐16). Compared with controls, patients with HCC demonstrated a significantly more prothrombotic hemostatic profile due to increased TG and reduced activation of fibrinolysis, independent of cirrhosis stage. During a median follow‐up of 175 days, 20 patients with decompensated cirrhosis developed further episodes of decompensation that were predicted by low FVII and high plasminogen activator inhibitor‐1 levels, independent of Model for End‐Stage Liver Disease score. Conclusion: Patients with cirrhosis with HCC have profound hyper‐coagulable changes that can account for their increased thrombotic tendency. In contrast, hypercoagulability in patients with decompensated cirrhosis is more likely a consequence of chronic liver disease rather than a driver for cirrhosis progression.